2009
DOI: 10.1021/es902622r
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Specific Determination of 4-Nonylphenols Using Comprehensive Two-Dimensional Gas Chromatography/Time-of-Flight Mass Spectrometry

Abstract: Technical nonylphenol (tNP), used for industrial production of nonylphenol polyethoxylate surfactants, is a complex mixture of C(3-10)-phenols. The major components, 4-nonylphenols, are weak endocrine disruptors whose estrogenicities vary according to the structure of the branched nonyl group. Thus, accurate risk assessment requires isomer-specific determination of 4-NPs. Comprehensive two-dimensional gas chromatography/time-of-flight mass spectrometry (GC x GC/ToFMS) was used to characterize tNP samples obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 32 publications
4
44
0
1
Order By: Relevance
“…Panić and Górecki reviewed GC×GC in environmental analyses and monitoring and they indicated that the main challenge in environmental analysis is that the analytes are usually present in trace amounts in very complex matrices (Panić & Górecki, 2006). In overcoming this problem, GC×GC-MS is a very powerful and attractive system that has been successfully applied for powerful identification of polychlorinated dibenzodioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) (de Vos et al, 2011), polychlorinated biphenyls (PCBs) (Focant et al, 2004;Hoh et al, 2007), polychlorinated naphthalenes (PCNs) (Korytár et al, 2005), nonyl phenol (NP) (Eganhouse, et al, 2009), benzothiazoles, benzotriazoles, benzosulfonamides (Jover et al, 2009), Cl-/Br-PAH congeners (Ieda et al, 2011), pharmaceuticals and pesticides (Matamoros et al, 2010) in complex environmental samples.…”
Section: Novel Gc Techniquesmentioning
confidence: 99%
“…Panić and Górecki reviewed GC×GC in environmental analyses and monitoring and they indicated that the main challenge in environmental analysis is that the analytes are usually present in trace amounts in very complex matrices (Panić & Górecki, 2006). In overcoming this problem, GC×GC-MS is a very powerful and attractive system that has been successfully applied for powerful identification of polychlorinated dibenzodioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) (de Vos et al, 2011), polychlorinated biphenyls (PCBs) (Focant et al, 2004;Hoh et al, 2007), polychlorinated naphthalenes (PCNs) (Korytár et al, 2005), nonyl phenol (NP) (Eganhouse, et al, 2009), benzothiazoles, benzotriazoles, benzosulfonamides (Jover et al, 2009), Cl-/Br-PAH congeners (Ieda et al, 2011), pharmaceuticals and pesticides (Matamoros et al, 2010) in complex environmental samples.…”
Section: Novel Gc Techniquesmentioning
confidence: 99%
“…Few applications of GC×GC were shortly reported (Eganhouse et al, 2009;Matamoros et al, 2010a;Hilton et al, 2010) and will be discussed in the present chapter. Recently, GC×GC applications devoted to measurement of volatile and semivolatile organic compounds in air and aerosol were reviewed and discussed (Arsene et al, 2011, Hamilton, 2010.…”
Section: Recent Applications Of Comprehensive Two-dimensional Gas Chrmentioning
confidence: 99%
“…GCGC was applied by Eganhouse et al (Eganhouse et al, 2009) to enhance the chromatographic resolution of highly similar compounds such as 4-nonylphenol isomers and facilitate identification of a number of previously unrecognized components. Among the 153-204 peaks attributed to alkylphenol, 59-664-NPs were identified (Figure 4).…”
Section: Alkyl Phenol Isomersmentioning
confidence: 99%
“…They indicated that the main challenge in environmental analysis is that the analytes are usually present in trace amounts in very complex matrices. In overcoming this hurdle, GC × GC-MS is a very powerful and attractive system that has been successfully applied for the many kinds of environmental pollutants, such as PCDDs, PCDFs, polychlorinated biphenyls (PCBs) [13,14], polychlorinated naphthalenes (PCNs) [15], nonyl phenol (NP) [16][17][18], benzothiazoles, benzotriazoles, benzosulfonamides [19], pharmaceuticals and pesticides [20]. In one such paper, Hoh et al suggested that GC × GC coupled with high speed TOF-MS (50 Hz) with unit-mass resolution has the potential to lower costs and allow for the faster analysis of minor environmental pollutants, such as PCDD/Fs over the current predominant method [14].…”
Section: Compoundsmentioning
confidence: 99%
“…For chlorinated anthracene or phenanthrene (C 14 H 10 ) and fluoranthene or pyrene (C 16 H 10 ) congeners, very small amounts of hepta chlorinated PAHs, were found in the soil sample. Also, for chlorinated benz[a]anthracene or chrysene (C 18 It suggested that there are a number of unconfirmed and highly substituted Cl-/Br-PAHs in the environmental samples as results of various reactions by chlorine, bromine and aromatic precursors (e.g., chlor-alkali processes, municipal waste incineration and automobile exhaust) [8,27]. Recently, Yamamoto et al reported that Cl-PAHs might have been formatted from brine electrolysis by graphite electrode abundantly contained pitch in the past [28].…”
Section: Identification Of Cl-/br-pahs Congeners and Other Organohalomentioning
confidence: 99%